Attitudes and experiences of university academic leaders - Ozkanli, O.; Bickley, Maureen; Fyfe, Sue; Lord, Linley (Ari Matbassi, 2008)
The main object of this paper is 10 investigate issues affecting women seeking academic leadership. The participants of the study were women academics and researchers a/lending an international research conference on women and leadership. The chosen methodology was a quantitative survey instrument with some qualitative open-ended questions based on an instrument developed for an earlier study already undertaken in Turkey. The surveys were statistically analysed with the open-ended questions allowing a further exploration of the issues from the respondents' perspectives. The results grouped around the themes of work and family, role conflict, attitudes and experiences towards gender discrimination in academic leadership issues, are reported in this study.